2008
DOI: 10.1021/ol7029189
|View full text |Cite
|
Sign up to set email alerts
|

A [4 + 2] Cycloaddition Strategy to Pyridine Boronic Ester Derivatives

Abstract: Alkynylboronate cycloadditions of 1,4-oxazin-2-ones and 2-pyrazinones provide a direct and regioselective route to functionalized pyridine boronic ester derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…7 In comparison, merged cycloaddition/cycloreversion approaches for the direct synthesis of 2-pyridones are not common; 8 however, Hoornaert and co-workers validated the possibility of this approach using cycloaddition of chlorinated pyrazinone intermediates. 9 The cycloreversion of the intermediate [2.2.2]diazabicycloadducts derived from these chlorinated pyrazinone precursors has two primary limitations: (1) extrusion of cyanide or cyanate derivatives requires high temperatures 10 (at or above 140 °C), and (2) extrusion is often nonselective and gives mixtures of both pyridine and pyridone products. 9 …”
mentioning
confidence: 99%
“…7 In comparison, merged cycloaddition/cycloreversion approaches for the direct synthesis of 2-pyridones are not common; 8 however, Hoornaert and co-workers validated the possibility of this approach using cycloaddition of chlorinated pyrazinone intermediates. 9 The cycloreversion of the intermediate [2.2.2]diazabicycloadducts derived from these chlorinated pyrazinone precursors has two primary limitations: (1) extrusion of cyanide or cyanate derivatives requires high temperatures 10 (at or above 140 °C), and (2) extrusion is often nonselective and gives mixtures of both pyridine and pyridone products. 9 …”
mentioning
confidence: 99%
“…Based on previous results from our group, we first investigated the use of microwave heating. 6 A slightly higher yield (47%) was obtained in 1 h at 70 °C with 2 equivalents of 5. We then screened the solvent, the temperature, the addition of an alcohol, 20 and the number of equivalents of 5 (Scheme 2).…”
mentioning
confidence: 92%
“…Fortunately, (S)mandelic acid (5) afforded a 36% yield. Next, we evaluated the use of (S)-O-acetylmandelic acid (6) and (S)-methyl mandelate (7). Since both compounds gave much lower yields than 5 (<10%), we demonstrated that both functional groups of the αhydroxyacid are necessary.…”
mentioning
confidence: 99%
“…Recent computational efforts suggest that oxazinones are the most reactive precursors for the [4 + 2] reaction component (of the tandem cycloaddition/cycloreversion sequence) and proceed readily with either electron-rich or electron-deficient substrates to yield pyridine products after loss of carbon dioxide . Because of the increased reactivity, 1,4-oxazinones are attractive substrates that can enable the use of less reactive 2π cycloaddition reaction components and/or permit use of milder reaction conditions . In this way, ubiquitous alkyne precursors may be used routinely and at reaction temperatures that are operationally convenient for the practicing chemist.…”
Section: Introductionmentioning
confidence: 99%